Landscape is a medium for regional planning (Ciudades, 2017)
Landscape has reappeared strongly in the contemporary culture, on both sides of the Atlantic. This recovery of the landscape concept comes, firstly, as a consequence of an increasing environmental and ecological concern, secondly, because of the pressure that the tourism exerts on specific areas, thirdly, because of the region´s efforts on maintaining their identity and finally because of the effects and the deep impact of the disperse and diffuse growth in the rural areas. This new strength of landscape concept has to do with the scope and the opportunities that it offers in the face of the traditional planning, the capacity to analyze and to theorize territories, ecosystems, nets and infrastructures, as well as of planning huge extents, emptied or urbanized. In the last few years, especially since the approval of the European Landscape Convention (Florence 2000), all the scales were incorporated in the strategic planning as tools of analysis and project. The Convention looks for a new glance of the territory, from the understanding of the existing one, of the patrimonial legacy (natural and cultural) that we have inherited and under the idea that we manage a fragile and dynamic resource.This text tries to reveal the keys of the landscape as key for regional planning in its double meaning as a place and as tool. The experiences developed in this article are just an example that we still have a very long way to go.
Keywords: regional planning; coastal management; management process; sustainable development; landscape urbanism; governance